Distances from the deep plantar arch to the lesser metatarsals at risk during osteotomy: a fresh cadaveric study - Ichiro Tonogai (Journal of Foot and Ankle Research, 2018)
Abstract Background The deep plantar arch is formed by anastomosis of the lateral and deep plantar arteries. Osteotomy of the lesser metatarsals is often used to treat metatarsalgia and forefoot deformity. Although it is known that some blood vessels supplying the lesser metatarsals are prone to damage during osteotomy, there is little information on the distances between the deep plantar arch and the three lesser metatarsals. The aims of this study were to identify the distances between the deep plantar arch and the lesser metatarsals and to determine how osteotomy could damage the arch. Methods Enhanced computed tomography scans of 20 fresh cadaveric feet (male, n = 10; female, n = 10; mean age 78.6 years at the time of death) were assessed. The specimens were injected with barium via the external iliac artery, and the distance from the deep plantar arch to each lesser metatarsal was measured on axial and sagittal images. Results The shortest distances from the deep plantar arch to the second, third, and fourth metatarsals in the axial plane were 0.5, 2.2, and 2.8 mm, respectively. The shortest distances from the distal epiphysis to a line passing through the deep plantar arch perpendicular to the longitudinal axis of the lesser metatarsal in the sagittal plane were 47.0, 45.7, and 46.4 mm, respectively, and those from the tarsometatarsal joint were 23.0, 21.0, and 18.6 mm. The deep plantar arch ran at the level of the middle third, within the proximal portion of this third in 11/20 (55.0%), 7/20 (35.0%), and 5/16 (31.2%) specimens, respectively, and at the level of the proximal third in 9/20 (45.0%), 13/20 (65.0%), and 11/16 (68.8%). Conclusions Overpenetration into the medial and plantar aspect of the second metatarsal or the proximal and plantar aspect of the fourth metatarsal during shaft or proximal osteotomy could easily damage the deep plantar arch. Shaft or proximal osteotomy approximately 45–47 mm proximal to the distal epiphysis or 18–23 mm distal to the tarsometatarsal joint on the plantar aspect could interrupt blood flow in the deep plantar arch.